Impact of Pesticide Usage on Potato Cultivation in Dhangadhi, Kailali, Sudurpashchim Pradesh, Nepal - Kathayat, Jang Bahadur (AMC Journal (Dhangadhi), 2024)
This research paper examines the impact of pesticide usage on potato cultivation in Dhangadhi, Kailali, Sudurpaschim Pradesh, Nepal, with a specific focus on the environmental and health consequences. The study utilises a descriptive and experimental research design to examine the inhibition of pesticide residue in potato crops. This is achieved through thorough sampling and analysis. The data collection process comprised of conducting interviews with local farmers and locals, as well as organising focus group talks to evaluate the level of awareness and the practices associated with pesticide usage. The study indicates that a substantial proportion of the local populace is cognizant of the detrimental impacts of pesticides, however only a minority consistently assesses soil fertility. The findings reveal diverse concentrations of pesticide residues in the samples obtained from the market, emphasising the necessity for more stringent rules and improved practices. Suggestions are given to alleviate the adverse effects of pesticide utilisation, fostering both food safety and environmental sustainability.